2020
DOI: 10.48550/arxiv.2006.05113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human brain activity for machine attention

Abstract: Cognitively inspired NLP leverages humanderived data to teach machines about language processing mechanisms. Recently, neural networks have been augmented with behavioral data to solve a range of NLP tasks spanning syntax and semantics. We are the first to exploit neuroscientific data, namely electroencephalography (EEG), to inform a neural attention model about language processing of the human brain with direct cognitive measures. Part of the challenge in working with EEG is that features are exceptionally ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…(Toneva and Wehbe 2019) use fMRI scans to interpret and improve BERT (Devlin et al 2018), a well-known transformer. Relatedly, (Muttenthaler, Hollenstein, and Barrett 2020) use EEG features to modify attention weights in an LSTM based model.…”
Section: Language Models and The Brainmentioning
confidence: 99%
“…(Toneva and Wehbe 2019) use fMRI scans to interpret and improve BERT (Devlin et al 2018), a well-known transformer. Relatedly, (Muttenthaler, Hollenstein, and Barrett 2020) use EEG features to modify attention weights in an LSTM based model.…”
Section: Language Models and The Brainmentioning
confidence: 99%
“…Brain-inspired computing is inspired by the human brain, which utilizes multiple types of information, such as visual, sound, and tactus, simultaneously to deal with tasks. Through interactions among various neural systems or neurons, the brain is capable of integrating diverse information while focusing on key elements ( Muttenthaler et al, 2020 ). This information processing approach of the brain has inspired the development of neural network-based multidimensional data fusion techniques ( LeCun et al, 2015 ), such as target detection ( Yuan et al, 2023 ), tracking ( Han et al, 2019a , 2022 ), and recognition ( Zeng et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Although covariate shift has been generally observed in brain signal data due to intra-and inter-subject variability (Lund et al 2005;Saha and Baumert 2020), previous work demonstrated promising transfer learning ability in brain signal decoding using deep learning models (Roy et al 2020;Zhang et al 2020;Makin, Moses, and Chang 2020). Furthermore, various studies (Muttenthaler, Hollenstein, and Barrett 2020;Hollenstein et al 2021Hollenstein et al , 2019Hale et al 2018;Schwartz and Mitchell 2019) have experimented with connecting brain signal decoding to NLP models, by either using brain signals as an additional modality for improving performance on NLP tasks or using NLP models to understand how the human brain encodes language.…”
Section: Introductionmentioning
confidence: 99%